Affective Topologies of Rural Youth Embodiment. Issue 1 (8th January 2015) - Farrugia, David; Smyth, John; Harrison, Tim
Abstract: This article explores the affective, embodied dimensions of young rural people's relationship with space and place. Relationship with space and place has been recognised as a significant dimension of rural youths' subjectivities but it has been primarily understood through representational perspectives which focus on young people's perceptions, images, or discursive constructions of their local places. In contrast, this article draws on non‐representational approaches to subjectivity and space to highlight the embodied, sensuous entanglements between young people's subjectivities and the spaces they have inhabited and experienced. Qualitative data gathered as part of a project exploring youths' subjectivities in regional Australia shows that young people's experience of their rural locale, as well as their relationship to the city, reflect an affective topology of relations of proximity and rhythmic tempo which emerges from the relationship between the space of their bodily hexis and the spaces and places they are situated within. These non‐representational, embodied processes are intrinsic to rural youths' subjectivities and structure how young people approach and navigate their futures.